PERANCANGAN APLIKASI ANDROID MUSEUM ADITYAWARMAN - RAHMADANTI J PUTRI, Dra. Zubaidah, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Nowadays, Android-based technology not only facilitates people to communicate but also leads them to search for various information and news. Android-based communication media is essential for people as it offers easiness and practicality for they with high mobility level.Today, various applications are created to promote places or travel destinations. A museum managed by Padang government by coordinating with West Sumatera Culture Service Agency named Museum Adityawarman, now is providing general information service about the museum. The service was completed with a user-friendly and high speed android-based application which eases people to get the information they need. Thus, they don’t need to access the museum’s website to get the information before they entering the museum.The application is programmed to read hybrid language and supported with Android Studio emulator. This Android-based mobile application is expected to be able to accommodate people with high mobility level receiving information, particularly the information about Museum Adityawarman.Keywords: Museum Adityawarman, Android-based application, Android Studio